2012
DOI: 10.1038/bjc.2012.503
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 receptors facilitate the progression of colon carcinoma within lung not within liver

Abstract: Background:Liver and lung metastases are the predominant cause of colorectal cancer (CRC)-related mortality. Chemokine-receptor pairs have a critical role in determining the metastatic progression of tumours. Our hypothesis was that disruption of CXCR7/CXCR7 ligands axis could lead to a decrease in CRC metastases.Methods:Primary tumours and metastatic tissues from patients with CRC were tested for the expression of CXCR7 and its ligands. Relevance of CXCR7/CXCR7 ligands for CRC metastasis was then investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 32 publications
(54 reference statements)
4
48
0
Order By: Relevance
“…Some studies have shown that CXCR-7 and IL-8 can contribute to tumor proliferation and metastasis in renal cell carcinoma (22). Activation of CXCR7 on tumor blood vessels facilitates the progression of colon cancer with lung metastasis (23). High expression of CXCR7 also leads to progression, metastasis and angiogenesis in brain tumors, and regulates the transendothelial migration in lymphoma (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that CXCR-7 and IL-8 can contribute to tumor proliferation and metastasis in renal cell carcinoma (22). Activation of CXCR7 on tumor blood vessels facilitates the progression of colon cancer with lung metastasis (23). High expression of CXCR7 also leads to progression, metastasis and angiogenesis in brain tumors, and regulates the transendothelial migration in lymphoma (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR7, as a recently discovered chemokine receptor, has demonstrated its characteristics in six aspects out of the ten top hallmarks of tumors, including resisting cell death, inducing angiogenesis, sustaining proliferative signaling, activating invasion and metastasis, tumor-promoting inflammation, and cancer-related genes [14,[17][18][19][20][21][22]. Both CXCR4 and CXCR7 are receptors of chemokine CXCL12 and have been reported in multiple tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…There are growing evidence pointing to chemokine involvement in these organ-selective metastases [14,15], and recently, a specific role of the CXCR7/chemokine axis has been demonstrated in lung compared to liver metastases [16]. However, the differential tropism from CRC to several target sites is still not well explained, including the mechanisms that drive hepatic homing.…”
Section: Metastasismentioning
confidence: 99%